2023
DOI: 10.5409/wjcp.v12.i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Higher rates of autism and attention deficit/hyperactivity disorder in American children: Are food quality issues impacting epigenetic inheritance?

Abstract: In the United States, schools offer special education services to children who are diagnosed with a learning or neurodevelopmental disorder and have difficulty meeting their learning goals. Pediatricians may play a key role in helping children access special education services. The number of children ages 6-21 in the United States receiving special education services increased 10.4% from 2006 to 2021. Children receiving special education services under the autism category increased 242% during the same period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 73 publications
(115 reference statements)
0
8
0
Order By: Relevance
“…Wang et al [ 76 ] found ultra-processed food consumption among United States youth aged 2-19 increased from 61.4% to 67% while the total caloric intake of whole or minimally processed foods decreased from 28.8% to 23.5% between 1999 and 2018. The increasing trends in ultra-processed food consumption among youth are alarming because strong evidence now suggests the consumption of ultra-processed foods is associated with heavy metal and pesticide exposures and the development of autism, developmental delay, and/or ADHD[ 42 ]. With the increasing ultra-processed food intake, we see increasing trends in the number of children struggling with these neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wang et al [ 76 ] found ultra-processed food consumption among United States youth aged 2-19 increased from 61.4% to 67% while the total caloric intake of whole or minimally processed foods decreased from 28.8% to 23.5% between 1999 and 2018. The increasing trends in ultra-processed food consumption among youth are alarming because strong evidence now suggests the consumption of ultra-processed foods is associated with heavy metal and pesticide exposures and the development of autism, developmental delay, and/or ADHD[ 42 ]. With the increasing ultra-processed food intake, we see increasing trends in the number of children struggling with these neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing ultra-processed food intake, we see increasing trends in the number of children struggling with these neurodevelopmental disorders. Dufault et al [ 42 ] reported a 242% increase in the number of children ages 6-21 in the United States receiving special education services under the autism category while student enrollment remained flat between 2006 and 2021. The need for special education services for children under the other health impaired (including ADHD) and developmental delay categories increased 83% and 184%, respectively, during the same period[ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a data analysis covering the period from 2006 to 2021, Dufault et al [ 25 ] found a significant increase in the number of children in the United States who required tutoring in specialized education due to learning difficulties. There was a 242% increase in cases of autism and 184% in developmental delays, as well as other health problems.…”
Section: Discussionmentioning
confidence: 99%